Correlation of comprehension reading skill and higher-order thinking skill with scientific literacy skill of senior high school biology teacher - Susiati, Asih; Adisyahputra, A; Miarsyah, Mieke (Biosfer: Jurnal Pendidikan Biologi, 2018)
The aim of this research was to determine the correlation between comprehension reading skill and higher-order thinking skill with scientific literacy skill for senior high school biology teacher. This research was conducted in Kabupaten Bekasi using 64 senior high school biology teachers as samples. Samples were taken by using Simple Random Sampling. The method used in this research was descriptive quantitative and research hypothesis tested by Pearson Product Moment in Î±=0,05. The results obtained correlation coefficient value between: comprehension reading skill with scientific literacy skill is 0.280; higher-order thinking skill with scientific literacy skill is 0.252; comprehension reading skill and higher-order thinking skill simultaneously with scientific literacy skill is 0.321. Coefficient of determination test showed that: 7,8% of comprehension reading skill contribute to scientific literacy skill; 6,4% of higher-order thinking skill contribute to scientific literacy skill; 10,3% of comprehension reading skill and higher-order thinking skill contribute to scientific literacy skill. Hope this result research can be a basic reference for further research.